Manajemen Sumber Daya Manusia dan Kepuasan Mahasiswa : Studi PPL STAI Kuala Kapuas 2024 - M. Zaini; Ushansyah Ushansyah; Olis Olis (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2025)
This article aims to analyze student satisfaction in the Field Experience Program (PPL) at STAI Kuala Kapuas in 2024, within the context of human resource management (HRM). Using a quantitative approach with a correlational method in a field research study, data were collected through questionnaires from 136 students as samples. The validity and reliability of the data were tested using factor analysis and Cronbach’s Alpha, with a value of 0.962, indicating a very high level of consistency. The research results showed a very strong positive correlation (Pearson Correlation = 0.894) between the effectiveness of HRM and student satisfaction in the PPL program. Factors such as recognition, supportive working conditions, supervision quality, and interpersonal relationships were found to be significant in creating a positive learning environment. Additionally, the structured PPL program, which included orientation, teaching practice, and seminars, contributed to meeting students' expectations.